Successful adaptation to higher education: The role of resilience and wellbeing in first-year students’ experiences (Journal of Student Affairs in Africa, 2026)
The first year of university marks a period of rapid and often challenging adjustments for young and developing individuals as they adapt to student life. Although this phase has proven to yield positive experiences for some students, resulting in personal and professional growth, it is also closely associated with the emergence and escalation of mental health issues, often as a consequence of difficulties experienced when individuals are transitioning into a dynamic new environment. Drawing from an interpretive description research design, the study aimed to obtain students’ qualitative description of resilience and wellbeing and its contribution to their psychosocial adaptation at a South African university. Three semi-structured, virtual focus group discussions (VFGDs) were conducted with 12 first-year student participants. The data were analysed using inductive thematic analysis. Two core themes were identified: (1) character strengths and personality; and (2) sense of belonging. These themes and their six sub-themes involved internal and external resources that contributed to students’ resilience and wellbeing and, ultimately, aided in their successful adaptation to university. The study’s findings present valuable insights for developing new policies and interventions geared towards enhancing the wellbeing of university students during the transition process.
Keywords: Higher education; resilience; wellbeing; student adaptation; qualitative